Laparoscopic Paraesophageal Hernia Repair and Pulmonary Embolism. Issue 6 (December 2019) - Davila, Daniel G.; Stetler, Jamil L.; Lin, Edward; Davis, Steven Scott; Yheulon, Christopher G.
Abstract : Objective: Pulmonary embolism (PE) following laparoscopic paraesophageal hernia repair (PEHR) is rare but occurs at a higher frequency than other laparoscopic procedures. We describe a series of patients who developed PEs after PEHR in hopes of capturing potential risk factors for further study. Materials and Methods: Five cases of PE after PEHR were observed between 2017 and 2018. Individual and perioperative risk factors, and postoperative courses were reviewed. Results: Patients had a mean age of 73 years (range, 59 to 86). All were female. Two patients presented acutely. Three patients underwent revisional surgery. The average procedure duration was 248 minutes (range, 162 to 324). All patients had gastrostomy tubes placed. The diagnosis of PE occurred within 3 to 19 days postoperatively. Four were treated with 3 months of oral anticoagulation; 1 was managed expectantly. Conclusions: Highly complex cases, marked by revisional status, need for mesh, large hernia size, and percutaneous endoscopic gastrostomy placement are likely at increased risk for PEs. Preoperative venous thromboembolism chemoprophylaxis should be considered in the majority of laparoscopic PEHR patients.